(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2020)
Multiprofessionelle Kooperation adressiert die gesteigerte schulische Komplexität in inklusiven Kontexten. Auf dieser Grundlage wurde das Vorbereitungsseminar „Inklusion – Kooperation in multiprofessionellen Teams in der Primarstufe“ an der Universität zu Köln konzipiert. Es handelt sich dabei um ein Kooperationsprojekt von Biwi, Sopäd, ZfL und ZfsL. Im Beitrag wird die strukturell-curriculare Verankerung der Lehrveranstaltung im Praxissemester sowie die inhaltliche Konzeption beschrieben. Multi-professional cooperation addresses the increased school complexity in inclusive contexts. On this basis, the preparatory seminar “Inclusion – Cooperation in Multiprofessional Teams in Primary School” was designed at the University of Cologne. It is a cooperation project between Educational Sciences, Special Education, the Center for Teacher Training and the Center for Practical School Teacher Training. The paper describes the structural and curricular anchoring of the course in the practical semester as well as the conception of content.